Modified negative electrode material, preparation method thereof, modified negative electrode and all-solid-state battery

By using a modified negative electrode material in a solid-state battery and using the first sulfide electrolyte to form an interface modification layer, the problem of poor compatibility between the negative electrode material and the electrolyte is solved, the cycle stability and energy density of the battery are improved, and the battery life is extended.

CN119133450APending Publication Date: 2024-12-13SHANGHAI XUANYI NEW ENERGY DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411044274.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-31
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

In existing solid-state batteries, the negative electrode materials have poor compatibility with sulfide electrolytes, which are prone to side reactions, resulting in poor electrical performance.

Method used

Using 90 to 99.9 parts of the negative electrode active material, 0.1 to 5 parts of the first sulfide electrolyte and optionally 0 to 5 parts of the lithium-containing additive, the interface modification layer is formed by the first sulfide electrolyte as the pre-stock raw material. Including Li3PO4 and Li2SO4, it improves interface stability and ionic conductivity and avoids the negative electrode reacting with the electrolyte.

Benefits of technology

It significantly improves the cycle stability of the negative electrode material and the volume energy density of the battery, reduces the interface impedance, and extends the battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133450A_ABST
    Figure CN119133450A_ABST
Patent Text Reader

Abstract

The invention provides a modified negative electrode material, a preparation method thereof, a modified negative electrode and an all-solid-state battery. The modified negative electrode material comprises the following raw materials: a negative electrode active material with specific content and specific type, a first sulfide electrolyte and an optional lithium-containing additive. According to the modified negative electrode material, the negative electrode active material, the first sulfide electrolyte and the optional lithium-containing additive are synergistic, the first sulfide electrolyte and the optional lithium-containing additive can be fully dispersed on the surface of the negative electrode active material, the thickness of an interface modification layer is uniform, and reaction between the negative electrode active material and the electrolyte can be effectively avoided; the stability of the interface between the negative electrode and the electrolyte is facilitated, the decomposition of the electrolyte in the circulating process can be effectively inhibited, and the development of the self capacity of the negative electrode active material is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of energy storage, and in particular to a modified negative electrode material, a preparation method thereof, a modified negative electrode and an all-solid-state battery. Background Art

[0002] In order to meet people's demand for high energy density and high safety of energy storage systems, solid-state batteries have shown great application potential in replacing traditional liquid batteries. In solid-state batteries, solid electrolytes are used as diaphragms, and silicon-based negative electrodes or metal lithium negative electrodes with high energy density are used on the negative electrode side. Therefore, solid-state batteries can significantly improve the energy density of the battery system. In addition, the lack of flammable electrolyte components in solid-state batteries can improve the safety of the battery system.

[0003] At present, the solid electrolytes with the greatest application potential are mainly sulfide electrolytes, oxide electrolytes and halide electrolytes. Among them, sulfide solid electrolytes are a type of electrolyte material with high ionic conductivity (1-25mS·cm -1 ), the development of sulfide-based solid-state batteries is the current mainstream development route.

[0004] However, the electrochemical window of sulfide electrolytes is narrow and their compatibility with negative electrode materials is poor. On the negative electrode side, the highly ionic conductive carbon material reacts with the sulfide electrolyte, which, on the one hand, causes the sulfide electrolyte to be decomposed, and on the other hand, causes the interface between the negative electrode and the electrolyte to be unstable. In addition, the ionic conductivity of the reaction product is low, which increases the interface resistance. 6 PS 5 For example, the electrolyte is at 1.71V (vs. Li + / Li) will undergo a reduction reaction, and the decomposition products are LiCl, Li 2 S and Li 3 P. During the decomposition process, the interface side reaction interface layer will affect the charge transfer and transmission at the interface due to its low ion conductivity, resulting in an increase in interface impedance. In addition, the spatial distribution of the decomposition products is usually uneven. As time goes by, the thickness of the interface layer will gradually increase, which will eventually affect the cycle performance of the battery. Summary of the invention

[0005] The main purpose of the present invention is to provide a modified negative electrode material, a preparation method thereof, a modified negative electrode and an all-solid-state battery, so as to solve the problems in the prior art that the negative electrode material has poor compatibility with the electrolyte, is prone to side reactions with the electrolyte, and leads to poor electrical performance.

[0006] In order to achieve the above object, according to one aspect of the present invention, a modified negative electrode material is provided, which comprises, by weight, 90 to 99.9 parts of a negative electrode active material, 0.1 to 5 parts of a first sulfide electrolyte and optionally 0 to 5 parts of a lithium-containing additive; wherein the negative electrode active material comprises one or more of graphite, hard carbon, soft carbon, silicon, silicon carbon and silicon oxygen; the first sulfide electrolyte comprises Li 4-x Ge 1-x P x S 4 、LPS、Li 6 PS 5 X, LiSiPSX and Li 11-a M 2-a P 1+a S 12 One or more of; X includes F, Cl, Br, I, O or Se, M includes one or more of Ge, Zn, Al, Ga, Si and Sn, 0≤x<1, 0.01≤a≤1; LPS includes Li 3 PS 4 , Li 7 P 3 S 11 and Li 9 P 3 S 12 One or more of.

[0007] In the modified negative electrode material of the present invention, an interface modification layer is provided on the outside of the negative electrode active material, which is mainly obtained by using the first sulfide electrolyte as a pre-material. The composition of the interface modification layer mainly includes Li 3 PO 4 , Li 2 SO 4 , among which Li 3 PO 4 , Li 2 SO 4 It has the characteristics of high ionic conductivity, can effectively reduce the interface impedance, and further helps to improve the battery cycle capacity. The interface modification layer uses the first sulfide electrolyte of a specific type of the present invention as a pre-raw material. Compared with other pre-raw materials, the first sulfide electrolyte of the present invention has good compatibility, so that the generated interface can also be compatible with a specific type of electrode material. In addition, the interface modification layer is dense and uniform, which can effectively avoid the reaction between the negative electrode active material and the electrolyte. On the one hand, it is beneficial to stabilize the interface between the negative electrode and the electrolyte. On the other hand, it can effectively inhibit the decomposition of the electrolyte during the circulation process, and is beneficial to the performance of the negative electrode active material's own capacity. The lithium-containing additive acts as a lithium source to supplement the lithium element. The additive and the first sulfide electrolyte work together to be more beneficial to Li 3 PO 4 , Li 2 SO4 The formation of a more dense and uniform interface modification layer is achieved.

[0008] The specific type of negative electrode active material of the present invention has a strong ability to carry and release lithium ions, and has good compatibility with the electrolyte, which is conducive to improving the cycle stability of the negative electrode material. The specific type of first sulfide electrolyte of the present invention has good ionic conductivity, and can cooperate with the specific type of negative electrode active material of the present invention, which is conducive to the reaction to obtain Li 3 PO 4 , Li 2 SO 4 The interface modification layer has high ionic conductivity.

[0009] Furthermore, the D50 of the negative electrode active material is 1 to 20 μm. Under the above conditions, the small particles of negative electrode material can be filled into the gaps of large particles, which is beneficial to increase the compaction density of the negative electrode sheet, thereby facilitating the improvement of the volume energy density of the battery.

[0010] Furthermore, the first sulfide electrolyte is selected from Li 6 PS 5 Cl and Li 3 PS 4 Mixture, Li 6 PS 5 Cl or Li 3 PS 4 ; When the first sulfide electrolyte is Li 6 PS 5 Cl and Li 3 PS 4 When the mixture is 6 PS 5 Cl and Li 3 PS 4 The molar ratio of is (0.1-10):1; and / or the D50 of the first sulfide electrolyte is 0.5-10 μm. The first sulfide electrolyte has a higher ionic conductivity and is more conducive to accelerating the transmission of interfacial charges. When used as a pre-material, the interface modification layer obtained includes Li 3 PO 4 , Li 2 SO 4 , LiCl and other main ingredients, which have better interface stability, and are more conducive to avoiding reactions between electrolytes and negative electrode materials.

[0011] Furthermore, the lithium-containing additive includes Li 2 O 2 , Li 2 O, LiOH, Li 2 CO 3 and Li 3BO 3 Preferably, the lithium-containing additive is selected from LiOH and Li 3 BO 3 Mixture, Li 2 O, LiOH or Li 2 CO 3 ; When the lithium-containing additive is LiOH and Li 3 BO 3 When mixed, LiOH and Li 3 BO 3 The molar ratio of is (0.1-10):1; and / or the D50 of the lithium-containing additive is 0.5-10 μm. The lithium-containing additive has better lithium ion transport properties and can provide more lithium elements for the interface modification layer, thereby being more conducive to improving interface charge transport / transfer.

[0012] Further, the modified negative electrode material includes 97-99 parts of negative electrode active material, 0.5-2 parts of the first sulfide electrolyte and 0.5-2 parts of the lithium-containing additive by weight; preferably, the mass ratio of the first sulfide electrolyte to the lithium-containing additive is (1-3): 1. Under the above conditions, the first sulfide electrolyte and the lithium-containing additive can be more fully dispersed on the surface of the negative electrode active material, the thickness of the interface modification layer is more uniform, the modification effect on the negative electrode active material is better, and it is conducive to further improving the cycle stability.

[0013] According to another aspect of the present invention, a method for preparing a modified negative electrode material is provided, comprising the following steps: mixing and annealing a negative electrode active material and a first sulfide electrolyte in sequence to obtain a modified negative electrode material. The preparation method of the present invention has a small number of processes, simple operation, low cost and easy availability of raw materials, a small interface impedance of the obtained modified negative electrode material, a dense and uniform interface modification layer formed on the surface, which can effectively avoid the reaction between the negative electrode active material and the electrolyte, is not only conducive to stabilizing the interface between the negative electrode and the electrolyte, but also can effectively inhibit the decomposition of the electrolyte during the circulation process, and is conducive to the use of the capacity of the negative electrode active material itself.

[0014] Furthermore, the preparation method also includes the step of mixing the lithium-containing additive with the negative electrode active material and the first sulfide electrolyte. The addition of the lithium-containing additive can provide more lithium elements, which is more conducive to Li 3 PO 4 , Li 2 SO 4 The resulting interface modification layer is denser and more uniform.

[0015] Further, the mixing method is one or more of ball milling, mechanical grinding and manual grinding; preferably, when the mixing method is ball milling, the ball milling speed is 50-500rpm, preferably 200-300rpm; and / or the ball milling time is 10-300min, preferably 30-120min; and / or the annealing temperature is 100-600°C, preferably 250-350°C; and / or the annealing time is 10-300min, preferably 30-120min. Under the above conditions, the raw materials are mixed more evenly, and the obtained interface modification layer is more dense and uniform.

[0016] According to another aspect of the present invention, a modified negative electrode is provided, comprising the modified negative electrode material or the modified negative electrode material prepared by the preparation method; preferably, the modified negative electrode comprises 70 to 90 parts of the modified negative electrode material, 10 to 20 parts of the second sulfide electrolyte, 0 to 2 parts of the conductive agent and 40 to 50 parts of the binder; more preferably, the second sulfide electrolyte comprises Li 6 PS 5 Cl, LiSiPSCl, Li 3 PS 4 , Li 7 P 3 S 11 and Li 9 P 3 S 12 One or more of; and / or the conductive agent includes one or more of carbon fiber, acetylene black, Ketjen black, carbon nanotube, graphene and carbon nanotube-graphene hybrid; and / or the binder includes one or more of styrene-butadiene-styrene triblock copolymer, polyvinyl pyrrolidone, polyurethane, polyethylene, polypropylene, polyvinylidene fluoride, sodium hydroxymethyl cellulose, styrene-butadiene rubber, sodium alginate and polyacrylic acid. The modified negative electrode material of the present invention not only has high ionic conductivity, but also has a stable interface between the negative electrode and the electrolyte, which is conducive to inhibiting the decomposition of the electrolyte during circulation, and can also effectively exert the capacity of the negative electrode material itself.

[0017] According to another aspect of the present invention, an all-solid-state battery is provided, comprising the modified negative electrode. The all-solid-state battery of the present invention has good cycle performance, good stability and long life.

[0018] In the modified negative electrode material of the present invention, an interface modification layer is provided on the outside of the negative electrode active material, which is mainly obtained by using the first sulfide electrolyte as a pre-material. The composition of the interface modification layer mainly includes Li 3 PO 4 , Li 2 SO 4 , among which Li 3 PO 4 , Li 2 SO 4It has the characteristics of high ionic conductivity, which can effectively reduce the interface impedance and further help improve the battery cycle capacity. The interface modification layer uses the first sulfide electrolyte as a pre-raw material. Compared with other pre-raw materials, the first sulfide electrolyte has the characteristics of good compatibility, which will make the interface compatible with the electrode material. In addition, the interface modification layer is dense and uniform, which can effectively avoid the reaction between the negative electrode active material and the electrolyte. On the one hand, it is beneficial to stabilize the interface between the negative electrode and the electrolyte. On the other hand, it can effectively inhibit the decomposition of the electrolyte during the circulation process, and is beneficial to the performance of the negative electrode active material's own capacity. The lithium-containing additive acts as a lithium source to supplement the lithium element. The additive and the first sulfide electrolyte work together to be more conducive to Li 3 PO 4 , Li 2 SO 4 to obtain a dense and uniform interface modification layer.

[0019] The specific content and specific type of negative electrode active material, the first sulfide electrolyte and the optional lithium-containing additive in the modified negative electrode material of the present invention work together. The first sulfide electrolyte and the optional lithium-containing additive can be fully dispersed on the surface of the negative electrode active material. The thickness of the interface modification layer is uniform, the modification effect on the negative electrode active material is good, and it is beneficial to improve the cycle stability of the negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0021] Figure 1 A schematic diagram of the preparation process of the modified negative electrode material according to Example 1 of the present invention is shown; and

[0022] Figure 2 A scanning electron microscope image of the modified negative electrode material according to Example 1 of the present invention is shown. DETAILED DESCRIPTION

[0023] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0024] As described in the background of the present invention, the prior art has the problem that the negative electrode material has poor compatibility with the electrolyte, is prone to side reactions with the electrolyte, and leads to poor electrical performance. In order to solve the above problems, in a typical embodiment of the present invention, a modified negative electrode material is provided, which comprises 90 to 99.9 parts of a negative electrode active material, 0.1 to 5 parts of a first sulfide electrolyte, and optionally 0 to 5 parts of a lithium-containing additive by weight; wherein the negative electrode active material comprises one or more of graphite, hard carbon, soft carbon, silicon, silicon carbon, and silicon oxygen; the first sulfide electrolyte comprises Li 4-x Ge 1-x P x S 4 、LPS、Li 6 PS 5 X, LiSiPSX and Li 11-a M 2-a P 1+a S 12 One or more of; X includes F, Cl, Br, I, O or Se, M includes one or more of Ge, Zn, Al, Ga, Si and Sn, 0≤x<1, 0.01≤a≤1; LPS includes Li 3 PS 4 , Li 7 P 3 S 11 and Li 9 P 3 S 12 Among them, the silicon carbon is preferably homogeneous silicon carbon.

[0025] In the modified negative electrode material of the present invention, an interface modification layer is provided on the outside of the negative electrode active material, which is mainly obtained by using the first sulfide electrolyte as a pre-material. The composition of the interface modification layer mainly includes Li 3 PO 4 , Li 2 SO 4 , among which Li 3 PO 4 , Li 2 SO 4It has the characteristics of high ionic conductivity, can effectively reduce the interface impedance, and further helps to improve the battery cycle capacity. The interface modification layer uses the first sulfide electrolyte of a specific type of the present invention as a pre-raw material. Compared with other pre-raw materials, the first sulfide electrolyte of the present invention has good compatibility, so that the generated interface can also be compatible with a specific type of electrode material. In addition, the interface modification layer is dense and uniform, which can effectively avoid the reaction between the negative electrode active material and the electrolyte. On the one hand, it is beneficial to stabilize the interface between the negative electrode and the electrolyte. On the other hand, it can effectively inhibit the decomposition of the electrolyte during the circulation process, and is beneficial to the performance of the negative electrode active material's own capacity. The lithium-containing additive acts as a lithium source to supplement the lithium element. The additive and the first sulfide electrolyte work together to be more beneficial to Li 3 PO 4 , Li 2 SO 4 The formation of a more dense and uniform interface modification layer is achieved.

[0026] The specific type of negative electrode active material of the present invention has a strong ability to carry and release lithium ions, and has good compatibility with the electrolyte, which is conducive to improving the cycle stability of the negative electrode material. The specific type of first sulfide electrolyte of the present invention has good ionic conductivity, and can cooperate with the specific type of negative electrode active material of the present invention, which is conducive to the reaction to obtain Li 3 PO 4 , Li 2 SO 4 The interface modification layer has high ionic conductivity.

[0027] The specific content and specific type of negative electrode active material, the first sulfide electrolyte and the optional lithium-containing additive in the modified negative electrode material of the present invention work together. The first sulfide electrolyte and the optional lithium-containing additive can be fully dispersed on the surface of the negative electrode active material. The thickness of the interface modification layer is uniform, the modification effect on the negative electrode active material is good, and it is beneficial to improve the cycle stability of the negative electrode material.

[0028] In a preferred embodiment, the D50 of the negative electrode active material is 1 to 20 μm. Under the above conditions, small particles of negative electrode material can be filled into the gaps of large particles, which is beneficial to increase the compaction density of the negative electrode sheet, thereby helping to improve the volume energy density of the battery. If the particle size of the negative electrode active material D50 is greater than 20 μm, it is not conducive to the capacity of the active material, and the battery performance effect is difficult to achieve the best state. If the particle size of the negative electrode active material D50 is less than 1 μm, it is not conducive to the charge transfer inside the electrode, and the charge transfer effect is difficult to achieve the best state. In a preferred embodiment, the D90 of the negative electrode active material is 3 to 40 μm.

[0029] In a preferred embodiment, the first sulfide electrolyte is selected from Li 6 PS5 Cl and Li 3 PS 4 Mixture, Li 6 PS 5 Cl or Li 3 PS 4 ; When the first sulfide electrolyte is Li 6 PS 5 Cl and Li 3 PS 4 When the mixture is 6 PS 5 Cl and Li 3 PS 4 The molar ratio of the first sulfide electrolyte is (0.1-10): 1. The first sulfide electrolyte has a higher ionic conductivity and is more conducive to accelerating the transmission of interfacial charges. The interface modification layer obtained when used as a pre-material includes Li 3 PO 4 , Li 2 SO 4 , LiCl and other main ingredients, which have better interface stability, and are more conducive to avoiding reactions between electrolytes and negative electrode materials.

[0030] In a preferred embodiment, the D50 of the first sulfide electrolyte is 0.5-10 μm. If the particle size of the first sulfide electrolyte D50 is greater than 10 μm or less than 0.5 μm, it is not conducive to uniform dispersion and the coating effect is difficult to achieve the best state. For similar reasons, in a preferred embodiment, the D90 of the first sulfide electrolyte is 1.5-15 μm.

[0031] In order to more fully supplement the lithium element, 3 PO 4 , Li 2 SO 4 The interface modification layer is more dense and uniform. In a preferred embodiment, the lithium-containing additive includes Li 2 O 2 , Li 2 O, LiOH, Li 2 CO 3 and Li 3 BO 3 In a preferred embodiment, the lithium-containing additive is selected from LiOH and Li 3 BO 3 Mixture, Li 2 O, LiOH or Li 2 CO 3 ; When the lithium-containing additive is LiOH and Li 3 BO 3 When mixed, LiOH and Li3 BO 3 The molar ratio is (0.1-10):1. The above-mentioned lithium-containing additive has better lithium ion transport properties and can provide more lithium elements for the interface modification layer, which is more conducive to improving the interface charge transport / transfer. In a preferred embodiment, the D50 of the lithium-containing additive is 0.5-10μm. If the particle size of the lithium-containing additive D50 is greater than 10μm or less than 0.5μm, it is not conducive to uniform dispersion, and the dispersion effect is difficult to achieve the best state. Based on similar reasons, in a preferred embodiment, the D90 of the lithium-containing additive is 0.8-8μm.

[0032] In order to make the components in the raw materials contact and react more fully, and make the first sulfide electrolyte and the lithium-containing additive more fully dispersed on the surface of the negative electrode active material, so as to be more conducive to improving the modification effect of the negative electrode active material and improving the cycle stability, in a preferred embodiment, the modified negative electrode material includes 97 to 99 parts of the negative electrode active material, 0.5 to 2 parts of the first sulfide electrolyte and 0.5 to 2 parts of the lithium-containing additive by weight; preferably, the mass ratio of the first sulfide electrolyte to the lithium-containing additive is (1 to 3): 1. Under the above conditions, the first sulfide electrolyte and the lithium-containing additive can be more fully dispersed on the surface of the negative electrode active material, the thickness of the interface modification layer is more uniform, the modification effect on the negative electrode active material is better, and it is conducive to further improving the cycle stability.

[0033] In another typical embodiment of the present invention, a method for preparing the modified negative electrode material of the present invention is also provided, wherein the negative electrode active material and the first sulfide electrolyte are sequentially mixed and annealed to obtain the modified negative electrode material. First, the first sulfide electrolyte is deposited on the surface of the negative electrode active material by mixing, and then annealing is performed, and the first sulfide electrolyte is oxidized to Li 3 PO 4 , Li 2 SO 4 Li et al. 3 PO 4 , Li 2 SO 4 etc. are attached to the surface of the negative electrode active material to form a dense and uniform interface modification layer.

[0034] The preparation method of the present invention has fewer processes, simple operation, low cost and easy availability of raw materials, the obtained modified negative electrode material has small interface impedance, and the interface modification layer formed on the surface is dense and uniform, which can effectively avoid the reaction between the negative electrode active material and the electrolyte, and is not only beneficial to stabilizing the interface between the negative electrode and the electrolyte, but also can effectively inhibit the decomposition of the electrolyte during the circulation process, and is beneficial to the performance of the capacity of the negative electrode active material itself.

[0035] In a preferred embodiment, the preparation method further comprises the step of mixing a lithium-containing additive with the negative electrode active material and the first sulfide electrolyte. The addition of the lithium-containing additive can provide more lithium elements, which is more conducive to the Li 3 PO 4 , Li 2 SO 4 The resulting interface modification layer is denser and more uniform.

[0036] In order to make the raw materials mixed more evenly, so that the interface modification layer is more dense and uniform, in a preferred embodiment, the mixing method is one or more of ball milling, mechanical grinding and manual grinding; preferably, when the mixing method is ball milling, the ball milling speed is 50-500rpm, preferably 200-300rpm; and / or the ball milling time is 10-300min, preferably 30-120min. If the ball milling speed is faster or the ball milling time is longer, not only more energy is consumed, but also the raw material component particles are smaller, which is not conducive to maintaining the integrity of the structure. If the ball milling speed is slower or the ball milling time is shorter, the raw material components are mixed unevenly, resulting in uneven thickness of the interface modification layer.

[0037] In a preferred embodiment, the annealing temperature is 100-600°C, preferably 250-350°C; and / or the annealing time is 10-300 min, preferably 30-120 min. If the annealing temperature is too high or the annealing time is longer, the composition and structure of the negative electrode material will be damaged, which is not conducive to the performance of the negative electrode material capacity. If the annealing temperature is too low or the annealing time is shorter, it is not conducive to the Li 3 PO 4 , Li 2 SO 4 The formation of the interface modification layer results in that the negative electrode active material cannot be completely coated, thereby failing to effectively prevent the negative electrode active material from reacting with the electrolyte. In a preferred embodiment, the annealing atmosphere is air or oxygen. Under this condition, it is more conducive to the full reaction of the raw materials with oxygen, thereby being more conducive to the Li 3 PO 4 , Li 2 SO 4 Generation of.

[0038] In another typical embodiment of the present invention, a modified negative electrode is also provided, comprising the modified negative electrode material or the modified negative electrode material prepared by the above preparation method; preferably, the modified negative electrode comprises 70 to 90 parts of the modified negative electrode material, 10 to 20 parts of the second sulfide electrolyte, 0 to 2 parts of the conductive agent and 40 to 50 parts of the binder; more preferably, the second sulfide electrolyte comprises Li 6 PS 5 Cl, LiSiPSCl, Li 3 PS4 , Li 7 P 3 S 11 and Li 9 P 3 S 12 One or more of; and / or the conductive agent includes one or more of carbon fiber, acetylene black, Ketjen black, carbon nanotube, graphene and carbon nanotube-graphene hybrid; and / or the binder includes one or more of styrene-butadiene-styrene triblock copolymer, polyvinyl pyrrolidone, polyurethane, polyethylene, polypropylene, polyvinylidene fluoride, sodium hydroxymethyl cellulose, styrene-butadiene rubber, sodium alginate and polyacrylic acid. The modified negative electrode of the present invention not only has high ionic conductivity, but also has a stable interface with the electrolyte, which is conducive to inhibiting the decomposition of the electrolyte during circulation, and can also effectively exert the capacity of the negative electrode material itself.

[0039] In another typical embodiment of the present invention, an all-solid-state battery is provided, comprising the modified negative electrode. The all-solid-state battery of the present invention has good cycle performance, good stability and long life.

[0040] Typically but not limiting, D50 of the negative electrode active material is 1 μm, 5 μm, 10 μm, 15 μm, 20 μm or a range consisting of any two of them.

[0041] Typical but not limiting, Li 11-a M 2-a P 1+a S 12 , a is 0.01, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1 or a range consisting of any two of them.

[0042] Typical but not limiting, Li 4-x Ge 1-x P x S 4 , x is 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or a range consisting of any two of them.

[0043] Typically, but not limiting, the first sulfide electrolyte is Li 6 PS 5 Cl and Li 3 PS 4 When the mixture is 6 PS 5 Cl and Li 3 PS 4The molar ratio is 0.1:1, 0.5:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1 or a range consisting of any two of them.

[0044] Typically but not limiting, the D50 of the first sulfide electrolyte is 0.5 μm, 1 μm, 5 μm, 10 μm, or a range consisting of any two of them.

[0045] Typical, but not limiting, lithium-containing additives are LiOH and Li 3 BO 3 When mixed, LiOH and Li 3 BO 3 The molar ratio is 0.1:1, 0.5:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1 or a range consisting of any two of them.

[0046] Typically, but not limited to, the D50 of the lithium-containing additive is 0.5 μm, 1 μm, 5 μm, 10 μm, or a range consisting of any two of these values.

[0047] Typically but not limiting, by mass percentage, the negative electrode active material accounts for 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 99.9% or a range consisting of any two of the raw materials; the first sulfide electrolyte accounts for 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5% or a range consisting of any two of the raw materials; the lithium-containing additive accounts for 0, 0.5%, 1%, 1.5%, 2%, 3%, 4%, 5% or a range consisting of any two of the raw materials.

[0048] Typically but not limiting, the mass ratio of the first sulfide electrolyte to the lithium-containing additive is 1:1, 1.5:1, 2:1, 2.5:1, 3:1 or a range consisting of any two of them.

[0049] Typically, but not limiting, the annealing temperature is 100°C, 200°C, 250°C, 300°C, 350°C, 400°C, 500°C, 600°C or a range consisting of any two of them; the annealing time is 10 min, 30 min, 60 min, 90 min, 120 min, 150 min, 180 min, 210 min, 240 min, 270 min, 300 min or a range consisting of any two of them.

[0050] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0051] Example 1

[0052] The schematic diagram of the preparation process of modified negative electrode materials is shown in Figure 1 .

[0053] The raw materials include 99% of the negative electrode active material (graphite, D50 = 8 μm) and 1% of the first sulfide electrolyte (Li 3 PS 4 , D50=2μm).

[0054] The raw materials were ball-milled at a rotation speed of 300 rpm for 60 minutes to make the raw materials uniformly mixed. Then, the raw materials were annealed at 300°C for 60 minutes in an air atmosphere to obtain a modified negative electrode material. Among them, in the modified negative electrode material, the outermost layer of the negative electrode active material is coated with an interface layer, which mainly includes Li 3 PO 4 , Li 2 SO 4 The thickness of the interface layer is uniform, about 90nm. The SEM image of the modified negative electrode material is shown in Figure 2 .

[0055] By weight, 80 parts of modified negative electrode material, 15 parts of second sulfide electrolyte (Li 6 PS 5 Cl), 1 part of conductive agent (vapor-grown carbon fiber), and 45 parts of binder (styrene-butadiene-styrene triblock copolymer) are dispersed in a solvent (anisole) to obtain a negative electrode slurry, and the solid content of the negative electrode slurry is controlled to be 55%. The negative electrode slurry is coated on the surface of the copper foil with a coating thickness of 65μm, and then dried at 60°C for 10h to obtain a modified negative electrode. The modified negative electrode is used to assemble an all-solid-state battery, and the electrochemical performance is tested.

[0056] Example 2

[0057] The only difference from Example 1 is:

[0058] The first sulfide electrolyte is Li 6 PS 5 In the obtained modified negative electrode material, the outermost layer of the negative electrode active material is coated with an interface layer, which mainly includes Li 3 PO 4 , Li 2 SO 4 , LiCl composition, the thickness of the interface layer is uniform, about 95nm.

[0059] Example 3

[0060] The only difference from Example 1 is:

[0061] The first sulfide electrolyte is Li 6 PS 5 Cl and Li 3 PS 4 A mixture of Li 6 PS 5 Cl and Li 3 PS 4 The molar ratio of is 1:1. In the obtained modified negative electrode material, the outermost layer of the negative electrode active material is coated with an interface layer, which mainly includes Li 3 PO 4 , Li 2 SO 4 , LiCl composition, the thickness of the interface layer is uniform, about 86nm.

[0062] Example 4

[0063] The only difference from Example 1 is:

[0064] The modified negative electrode material raw material includes 98.5% of negative electrode active material (graphite, D50 = 8 μm), 1% of the first sulfide electrolyte (Li 6 PS 5 Cl, D50 = 2 μm) and 0.5% lithium-containing additive (LiOH, D50 = 1 μm), the mass ratio of the first sulfide electrolyte to the additive is 2:1. In the obtained modified negative electrode material, the outermost layer of the negative electrode active material is coated with an interface layer, which mainly includes Li 3 PO 4 , Li 2 SO 4 、LiCl、Li 2 O component, the thickness of the interface layer is uniform, about 89nm.

[0065] Example 5

[0066] The only difference from Example 4 is that:

[0067] The modified negative electrode material raw material includes 98.5% of negative electrode active material (graphite, D50 = 8 μm), 1% of the first sulfide electrolyte (Li 6 PS 5 Cl, D50 = 2 μm) and 0.5% lithium-containing additives (LiOH and Li 3 BO 3 Mixture, LiOH and Li 3 BO 3The molar ratio of the first sulfide electrolyte to the additive is 1:1, D50 = 1 μm), and the mass ratio of the first sulfide electrolyte to the additive is 2:1. In the obtained modified negative electrode material, the outermost layer of the negative electrode active material is coated with an interface layer, and the interface layer mainly includes Li 3 PO 4 , Li 2 SO 4 、LiCl、Li 2 O. Li 3 BO 3 The composition and thickness of the interface layer are uniform, about 86nm.

[0068] Example 6

[0069] The only difference from Example 4 is that:

[0070] The modified negative electrode material raw material includes 98.5% of the negative electrode active material (homogeneous silicon carbon, D50 = 9 μm), 1% of the first sulfide electrolyte (Li 6 PS 5 Cl, D50 = 2 μm) and 0.5% lithium-containing additive (LiOH, D50 = 1 μm), the mass ratio of the first sulfide electrolyte to the additive is 2:1. In the obtained modified negative electrode material, the outermost layer of the negative electrode active material is coated with an interface layer, which mainly includes Li 3 PO 4 , Li 2 SO 4 、LiCl、Li 2 O component, the thickness of the interface layer is uniform, about 105nm.

[0071] Example 7

[0072] The only difference from Example 4 is that:

[0073] The modified negative electrode material raw material includes 98.5% of the negative electrode active material (homogeneous silicon carbon, D50 = 9 μm), 1% of the first sulfide electrolyte (Li 6 PS 5 Cl, D50 = 2 μm) and 0.5% lithium-containing additive (Li 3 BO 3 , D50 = 1 μm), the mass ratio of the first sulfide electrolyte to the additive is 2:1. In the obtained modified negative electrode material, the outermost layer of the negative electrode active material is coated with an interface layer, and the interface layer mainly includes Li 3 PO 4 , Li 2 SO 4 、LiCl、Li 3 BO 3 The composition and thickness of the interface layer are uniform, about 107nm.

[0074] Example 8

[0075] The only difference from Example 4 is that:

[0076] The modified negative electrode material raw material includes 90% of negative electrode active material (graphite, D50 = 8 μm), 5% of the first sulfide electrolyte (Li 6 PS 5 Cl, D50 = 2 μm) and 5% lithium-containing additive (Li 2 O, D50 = 1 μm), the mass ratio of the first sulfide electrolyte to the additive is 1:1. In the obtained modified negative electrode material, the outermost layer of the negative electrode active material is coated with an interface layer, and the interface layer mainly includes Li 3 PO 4 , Li 2 SO 4 , LiCl composition, the thickness of the interface layer is uniform, about 513nm.

[0077] Example 9

[0078] The only difference from Example 3 is that:

[0079] The modified negative electrode material raw material includes 99% of negative electrode active material (graphite, D50 = 8 μm), 0.5% of the first sulfide electrolyte (Li 6 PS 5 Cl and Li 3 PS 4 Mixture, Li 6 PS 5 Cl and Li 3 PS 4 The molar ratio of the first sulfide electrolyte to the additive is 1:1, D50 = 2 μm) and 0.5% of a lithium-containing additive (LiOH, D50 = 1 μm), and the mass ratio of the first sulfide electrolyte to the additive is 1:1. In the obtained modified negative electrode material, the outermost layer of the negative electrode active material is coated with an interface layer, which mainly includes Li 3 PO 4 , Li 2 SO 4 , LiCl composition, the thickness of the interface layer is uniform, about 60nm.

[0080] Example 10

[0081] The only difference from Example 1 is:

[0082] The modified negative electrode material raw material was ball milled at a rotation speed of 50 rpm for 300 min to make the raw materials uniformly mixed. Then, the raw materials were annealed at 100°C for 300 min in an air atmosphere to obtain a modified negative electrode material. In the obtained modified negative electrode material, the outermost layer of the negative electrode active material is coated with an interface layer, which mainly includes Li 3 PO 4 , Li 2 SO 4 The composition and thickness of the interface layer are uniform, about 98nm.

[0083] By weight, 70 parts of modified negative electrode material, 20 parts of second sulfide electrolyte (Li 3 PS 4 ), 1 part of conductive agent (carbon nanotubes), and 50 parts of binder (sodium hydroxymethyl cellulose) are dispersed in a solvent (anisole) to obtain a negative electrode slurry, and the solid content of the negative electrode slurry is controlled to be 55%. The negative electrode slurry is coated on the surface of the copper foil with a coating thickness of 50 μm, and then dried at 60°C for 10 hours to obtain a modified negative electrode. The modified negative electrode is used to assemble an all-solid-state battery and the electrochemical performance is tested.

[0084] Embodiment 11

[0085] The only difference from Example 1 is:

[0086] The modified negative electrode material raw material was ball-milled at a rotation speed of 500 rpm for 10 minutes to make the raw materials uniformly mixed. Then, the raw materials were annealed at 600°C for 10 minutes in an oxygen atmosphere to obtain a modified negative electrode material. In the obtained modified negative electrode material, the outermost layer of the negative electrode active material is coated with an interface layer, which mainly includes Li 3 PO 4 , Li 2 SO 4 The composition and thickness of the interface layer are uniform, about 95nm.

[0087] By weight, 90 parts of modified negative electrode material, 10 parts of second sulfide electrolyte (Li 7 P 3 S 11 ), 2 parts of conductive agent (graphene), and 40 parts of binder (styrene-butadiene rubber) are dispersed in a solvent (anisole) to obtain a negative electrode slurry, and the solid content of the negative electrode slurry is controlled to be 55%. The negative electrode slurry is coated on the surface of the copper foil with a coating thickness of 80 μm, and then dried at 60°C for 10 hours to obtain a modified negative electrode. The modified negative electrode is used to assemble an all-solid-state battery and the electrochemical performance is tested.

[0088] Example 12

[0089] The only difference from Example 1 is:

[0090] The modified negative electrode material raw material was ball milled at a rotation speed of 200 rpm for 120 minutes to make the raw materials uniformly mixed. Then, the raw materials were annealed at 250°C for 120 minutes in an air atmosphere to obtain a modified negative electrode material. In the obtained modified negative electrode material, the outermost layer of the negative electrode active material is coated with an interface layer, which mainly includes Li 3 PO 4 , Li 2 SO 4 The composition and thickness of the interface layer are uniform, about 102nm.

[0091] Example 13

[0092] The only difference from Example 1 is:

[0093] The modified negative electrode material raw material was ball milled at a rotation speed of 300 rpm for 30 minutes to make the raw materials uniformly mixed. Then, the raw materials were annealed at 350°C for 30 minutes in an oxygen atmosphere to obtain a modified negative electrode material. In the obtained modified negative electrode material, the outermost layer of the negative electrode active material is coated with an interface layer, which mainly includes Li 3 PO 4 , Li 2 SO 4 The composition and thickness of the interface layer are uniform, about 103nm.

[0094] Comparative Example 1

[0095] The raw materials of the negative electrode material only contain graphite.

[0096] The raw material of the negative electrode material was ball-milled at a rotation speed of 300 rpm for 60 minutes to make the raw material uniformly mixed. Then, the raw material was annealed at 300° C. for 60 minutes in an air atmosphere to obtain the negative electrode material. In the obtained negative electrode material, the outermost layer of the negative electrode active material was not coated with an interface layer.

[0097] The negative electrode material is prepared through a wet process, the negative electrode is used to assemble an all-solid-state battery, and the electrochemical performance is tested.

[0098] Comparative Example 2

[0099] The only difference from Example 3 is that:

[0100] In terms of weight percentage, the raw materials of the modified negative electrode material include 98.5% of negative electrode active material (graphite, D50 = 8 μm), 1.5% of additives (Li 2 O, D50 = 1 μm). In the obtained modified negative electrode material, the outermost layer of the negative electrode active material is coated with an interface layer, which mainly includes Li 2O component, the thickness of the interface layer is uneven, about 122nm.

[0101] The test results of the electrochemical properties (reversible capacity, capacity retention rate) of the all-solid-state batteries prepared in the above embodiments and comparative examples are shown in Table 1.

[0102] Test method:

[0103] Reversible capacity: tested at 55℃, 0.2C.

[0104] Capacity retention rate: tested at 55°C, 0.2C.

[0105] Table 1

[0106]

[0107]

[0108] As can be seen from the above, the modified negative electrode material raw materials of Comparative Examples 1 and 2 do not contain sulfide electrolytes, and the prepared modified negative electrode materials have large interface impedance and poor battery cycle performance. Compared with the comparative examples, the specific type of raw materials of the present invention are used, and the interface modification layer obtained by mainly using the first sulfide electrolyte as the pre-raw material on the outside of the negative electrode active material in the modified negative electrode material can not only effectively reduce the interface impedance, but also effectively avoid the reaction between the negative electrode active material and the electrolyte, which is further conducive to improving the battery cycle capacity.

[0109] In addition, it can be seen that when the types, contents and process parameters of each raw material are within the preferred range of the present invention, the interface modification layer has better compatibility with the electrode material, and the interface modification layer is more dense and uniform, so that the reaction between the negative electrode active material and the electrolyte can be further effectively avoided, which is more conducive to the performance of the capacity of the negative electrode active material itself, and the electrochemical performance (reversible capacity, capacity retention rate) of the modified negative electrode material is higher. In addition, according to Examples 6 and 7, it can be seen that when the negative electrode active material in the negative electrode active material raw material is silicon carbon, the capacity of the negative electrode active material can be more fully utilized, and the reversible capacity of the battery is higher.

[0110] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A modified negative electrode material, It is characterized in that The invention comprises, by weight, 90 to 99.9 parts of a negative electrode active material, 0.1 to 5 parts of a first sulfide electrolyte, and optionally 0 to 5 parts of a lithium-containing additive; Wherein, the negative electrode active material includes one or more of graphite, hard carbon, soft carbon, silicon, silicon carbon and silicon oxygen; The first sulfide electrolyte includes Li 4-x Ge 1-x P x S 4 、LPS、Li 6 PS 5 X, LiSiPSX and Li 11-a M 2-a P 1+a S 12 One or more of; X includes F, Cl, Br, I, O or Se, M includes one or more of Ge, Zn, Al, Ga, Si and Sn, 0≤x<1, 0.01≤a≤1; LPS includes Li 3 PS 4 , Li 7 P 3 S 11 and Li 9 P 3 S 12 One or more of.

2. The modified negative electrode material according to claim 1, It is characterized in that The D50 of the negative electrode active material is 1 to 20 μm.

3. The modified negative electrode material according to claim 1 or 2, It is characterized in that The first sulfide electrolyte is selected from Li 6 PS 5 Cl and Li 3 PS 4 Mixture, Li 6 PS 5 Cl or Li 3 PS 4 ; When the first sulfide electrolyte is Li 6 PS 5 Cl and Li 3 PS 4 When the mixture is 6 PS 5 Cl and Li 3 PS 4 The molar ratio is (0.1-10):1; and / or The D50 of the first sulfide electrolyte is 0.5 to 10 μm.

4. The modified negative electrode material according to any one of claims 1 to 3, It is characterized in that The lithium-containing additive includes Li 2 O 2 , Li 2 O, LiOH, Li 2 CO 3 and Li 3 BO 3 One or more of; Preferably, the lithium-containing additive is selected from LiOH and Li 3 BO 3 Mixture, Li 2 O, LiOH or Li 2 CO 3 ; When the lithium-containing additive is LiOH and Li 3 BO 3 When mixed, LiOH and Li 3 BO 3 The molar ratio is (0.1-10):1; and / or The D50 of the lithium-containing additive is 0.5 to 10 μm.

5. The modified negative electrode material according to any one of claims 1 to 4, It is characterized in that The modified negative electrode material comprises, by weight, 97 to 99 parts of the negative electrode active material, 0.5 to 2 parts of the first sulfide electrolyte, and 0.5 to 2 parts of the lithium-containing additive; Preferably, the mass ratio of the first sulfide electrolyte to the lithium-containing additive is (1-3):

1.

6. A method for preparing a modified negative electrode material according to any one of claims 1 to 5, It is characterized in that The negative electrode active material and the first sulfide electrolyte are sequentially mixed and annealed to obtain the modified negative electrode material.

7. The preparation method according to claim 6, It is characterized in that The preparation method further includes the step of mixing the lithium-containing additive with the negative electrode active material and the first sulfide electrolyte.

8. The preparation method according to claim 6 or 7, It is characterized in that The mixing method is one or more of ball milling, mechanical milling and manual milling; Preferably, when the mixing method is ball milling, the ball milling speed is 50 to 500 rpm, preferably 200 to 300 rpm; and / or The ball milling time is 10 to 300 min, preferably 30 to 120 min; and / or The annealing temperature is 100 to 600°C, preferably 250 to 350°C; and / or The annealing time is 10 to 300 minutes, preferably 30 to 120 minutes.

9. A modified negative electrode, It is characterized in that A modified negative electrode material comprising any one of claims 1 to 5, or a modified negative electrode material prepared by the preparation method of any one of claims 6 to 8; Preferably, the modified negative electrode comprises 70 to 90 parts of the modified negative electrode material, 10 to 20 parts of a second sulfide electrolyte, 0 to 2 parts of a conductive agent and 40 to 50 parts of a binder; More preferably, the second sulfide electrolyte comprises Li 6 PS 5 Cl, LiSiPSCl, Li 3 PS 4 , Li 7 P 3 S 11 and Li 9 P 3 S 12 One or more of; and / or The conductive agent includes one or more of carbon fiber, acetylene black, Ketjen black, carbon nanotube, graphene and carbon nanotube-graphene hybrid; and / or The binder includes one or more of styrene-butadiene-styrene triblock copolymer, polyvinyl pyrrolidone, polyurethane, polyethylene, polypropylene, polyvinylidene fluoride, sodium hydroxymethyl cellulose, styrene-butadiene rubber, sodium alginate and polyacrylic acid.

10. An all-solid-state battery, It is characterized in that Comprising the modified negative electrode as claimed in claim 9.